Minor contribution of small thaw ponds to the pools of carbon and methane in the inland waters of the permafrost-affected part of the Western Siberian Lowland. (16th March 2018) - Polishchuk, Y M; Bogdanov, A N; Muratov, I N; Polishchuk, V Y; Lim, A; Manasypov, R M; Shirokova, L S; Pokrovsky, O S
Abstract: Despite the potential importance of small (< 1000 m 2 ) thaw ponds and thermokarst lakes in greenhouse gas (GHG) emissions from inland waters of high latitude and boreal regions, these features have not been fully inventoried and the volume of GHG and carbon in thermokarst lakes remains poorly constrained. This is especially true for the vast Western Siberia Lowland (WSL) which is subject to strong thermokarst activity. We assessed the number of thermokarst lakes and their size distribution for the permafrost-affected WSL territory based on a combination of medium-resolution Landsat-8 images and high-resolution Kanopus-V scenes on 78 test sites across the WSL in a wide range of lake sizes (from 20 to 2 × 10 8 m 2 ). The results were in fair agreement with other published data for world lakes including those in circum-polar regions. Based on available measurements of CH4, CO2, and dissolved organic carbon (DOC) in thermokarst lakes and thaw ponds of the permafrost-affected part of the WSL, we found an inverse relationship between lake size and concentration, with concentrations of GHGs and DOC being highest in small thaw ponds. However, since these small ponds represent only a tiny fraction of the landscape (i.e. 1.5% of the total lake area), their contribution to the total pool of GHG and DOC in inland lentic water of the permafrost-affected part of the WSL is less than 2%. As such, despite high concentrations of DOC and GHG in small ponds, their role in overall C storage can be negated. Ongoing lake drainage due to climate warming and permafrost thaw in the WSL may lead to a decrease in GHG emission potential from inland waters and DOC release from lakes to rivers.